The effect of quality of educational resources on mathematics achievement: Turkish Case from PISA-2006 - Demir, Ibrahim; Unal, Hasan; Kilic, Serpil (ELSEVIER SCIENCE BV, 2010)
The purpose of this study was to examine quality of educational resources both technological (computers, software, etc.) and non- technological (textbooks, workbooks, etc..) on mathematics achievement of Turkish students. The sample was a total of 4942, 15- years old Turkish students, participated in PISA 2006 study. The participants completed a questionnaire and participated in mathematics test. ANOVA and MANOVA used to identify effect of educational resources on mathematics achievement. Results revealed that, shortage or inadequacy of computers effected students' mathematics achievement. Furthermore, the better library materials are, the higher the mathematics achievement. A lack of qualified mathematics teacher was a factor in students mathematics achievement. Results indicated that both technological and non- technological educational resources are important in students' mathematics achievement. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Computers; educational software; educational materials; mathematics achievement; PISA 2006; Education & Educational Research